2012
DOI: 10.3168/jds.2011-5216
|View full text |Cite
|
Sign up to set email alerts
|

Producer survey of bird-livestock interactions in commercial dairies

Abstract: The objective of this producer survey was to identify and estimate damage caused by bird-livestock interactions in commercial dairies. The interactions between birds and livestock have previously been implicated in causing economic damage while contributing to the environmental dissemination of microorganisms pathogenic to livestock and humans. Very little research exists to help producers understand what bird species use dairies, why they use dairies, or the scope and nature of damage created as a result of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…environmental dissemination of antimicrobial resistant (AMR) bacteria. Wildlife incursions into CAFO are known to cause economic damage as a consequence of feed consumption (Shwiff et al, 2012) and many of these species have been documented as carriers of E. coli O157:H7 and AMR S. enterica (Kirk et al, 2002;Gaukler et al, 2009;Kauffman and LeJeune, 2011). European starlings (Sturnus vulgaris) in particular are known to cause damage to CAFO through the consumption of livestock feed (Dolbeer et al, 1978;Depenbusch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…environmental dissemination of antimicrobial resistant (AMR) bacteria. Wildlife incursions into CAFO are known to cause economic damage as a consequence of feed consumption (Shwiff et al, 2012) and many of these species have been documented as carriers of E. coli O157:H7 and AMR S. enterica (Kirk et al, 2002;Gaukler et al, 2009;Kauffman and LeJeune, 2011). European starlings (Sturnus vulgaris) in particular are known to cause damage to CAFO through the consumption of livestock feed (Dolbeer et al, 1978;Depenbusch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the ecological interactions between synanthropic birds and cattle also contribute to increased cattle fecal shedding and environmental contamination of CAFO with S. enterica, Escherichia coli O157:H7 and Mycobacterium avium spp. paratuberculosis Daniels et al, 2003;Carlson et al, 2011a;Kauffman and LeJeune, 2011;Shwiff et al, 2012). European starlings (Sturnus vulgaris) stand out as a potential source for E. coli O157:H7 and S. enterica in CAFO (Carlson et al, 2011b;Cernicchiaro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reptiles (e.g., Burmese pythons and Brown tree snakes) and other aquatic nonnatives typically cause economic impact through depredation and environmental destruction but rarely through disease transmission (Greene et al 2007;Snow et al 2007). Some avian species, such as starlings, can create impacts in all three categories through depredation of crops, destruction of property (e.g., statues, bridges, buildings), and disease transmission (e.g., fecal contamination of livestock feed) (Shwiff et al 2012). A substantial portion of the overall impact of avian VIS tends to be through depredation of crops, while the other two categories of damage tend to contribute signi cantly less to the overall impact.…”
Section: Framing the Economic Impacts Of Vertebrate Invasive Species mentioning
confidence: 99%
“…Shwiff et al (2012) used data from the snake's invasion on Guam, along with survey information from Hawaii, to estimate the cost of a potential invasion into Hawaii. Results suggested that total annual damage from such an invasion would be between $593 million and $2.14 billion.…”
Section: Vis Except Feral Swinementioning
confidence: 99%